Time marker for the late pleistocene in Peninsular Malaysia: Study of the volcanic ash deposits / Norishah Binti Hashim - Hashim, Norishah (2014)

(untitled)
A detailed study was conducted on the tephra deposits that were found in several locations in the Peninsular Malaysia which are important time markers in the local Quaternary stratigraphy. Typically, these deposits consisted of aerially deposited, fine-grained < 100 μm, silica-rich volcanic glass shards and mineral grains, in layers ranging from 10 cm to 9 m in thickness, within quaternary lacustrine sediments. Few of these have been dated. In the literature, most, if not all, were attributed to the VEI 8 eruption at Lake Toba at 70-75 k.a., while, in actuality, there have been three other high VEI eruptions in Sumatra that might have been responsible - Mount Maninjau at 80 and 52 k.a. (proximal tuffs are exposed at Sianok Canyon near Padang Highlands, Sumatra) and Lake Ranau between 0.7 and 0.4 m.a. In this study, site reconnaissance, tephra age determination and geochemical fingerprint analysis have been carried out to provide scientific proves of the origins of Peninsular Malaysia tephra. Detailed field mapping of tephra distribution in the vicinity of Lenggong in Perak revealed that the tephra layers, covering 15 km2, were deposited at a time when the local stream base level was 70 m above the current level, as most of the fresh tephra layers were found at that elevation. Tephra distribution was controlled by topography at the time of deposition since layers of fresh and reworked deposits of tephra had been discovered in the vicinity of the Perak River banks and on gentle slopes of palm oil estates. The presence of reworked ash under layers of fresh ash might indicated that more than one paroxysmal eruption were responsible. Fission track and optically stimulated luminescence (OSL) techniques were executed on two selected areas with fresh layers of tephra and correlated the results with published data of possible origins. Cluster analysis, bivariate analysis, Rare-Earth Element and trace element ratios analysis and spider diagrams were implemented to differentiate and recognize individual eruptions. The results of fission track dates of Lenggong tephra were 59 ± 7 k.a. and 59 ± 9 k.a., while Kuala Pelus tephra had luminescence dates of 58.5 ± 7.6 k.a and 75.5 ± 9.8 k.a. These dates could be correlated with the 52 k. a. Maninjau and 75 k. a. Toba eruptions. Major and trace element content of glass shards revealed similarities between those from the Peninsular Malaysia and the proximal tuff from the 75 k.a. Toba eruption. The majority of Gelok samples were correlated to Toba sample. Even though Lenggong and Padang Sanai major elements result showed that there were three populations in the same layer, chemical genetically it could not be related with Maninjau samples. Kg. Dong and Kuala Kangsar tephra showed the largest variations of SiO2 and alkalies which were distinct from the other Peninsular Malaysia tephra. The Maninjau tuff was distinctly different from the Peninsular Malaysia tephra and from the YTT. This implies that Lenggong tephra could be originated from Toba and other possible source(s). The conclusion that could be drawn from this evidences that it is significantly proved that the tephra in Peninsular Malaysia is most likely originated from Toba and also possible from Maninjau and other eruptions.